2018
DOI: 10.1155/2018/1482795
|View full text |Cite
|
Sign up to set email alerts
|

Low Autophagy (ATG) Gene Expression Is Associated with an Immature AML Blast Cell Phenotype and Can Be Restored during AML Differentiation Therapy

Abstract: Autophagy is an intracellular degradation system that ensures a dynamic recycling of a variety of building blocks required for self-renewal, homeostasis, and cell survival under stress. We used primary acute myeloid leukemia (AML) samples and human AML cell lines to investigate the regulatory mechanisms of autophagy and its role in AML differentiation. We found a significantly lower expression of key autophagy- (ATG-) related genes in primary AML as compared to healthy granulocytes, an increased autophagic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 71 publications
8
60
0
Order By: Relevance
“…These data were consistent with studies showing that defective autophagy lead to a distinct reduction in granules and nuclear lobularization, as well as defective differentiation and dysfunction of neutrophils. [33][34][35] To further determine the role of autophagy in A. fumigatus keratitis, the levels of inflammatory cytokines IL-1β, IL-18, HMGB1, TNF-α, and IL-10 were detected after treatment with 3-MA, CQ, and rapamycin. Results indicated that treatment with 3-MA and CQ significantly increased mRNA and protein levels of IL-1β, IL-18, HMGB1, and TNF-α, and reduced the expression of IL-10 in comparison with infected control corneas.…”
Section: Discussionmentioning
confidence: 99%
“…These data were consistent with studies showing that defective autophagy lead to a distinct reduction in granules and nuclear lobularization, as well as defective differentiation and dysfunction of neutrophils. [33][34][35] To further determine the role of autophagy in A. fumigatus keratitis, the levels of inflammatory cytokines IL-1β, IL-18, HMGB1, TNF-α, and IL-10 were detected after treatment with 3-MA, CQ, and rapamycin. Results indicated that treatment with 3-MA and CQ significantly increased mRNA and protein levels of IL-1β, IL-18, HMGB1, and TNF-α, and reduced the expression of IL-10 in comparison with infected control corneas.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the interplay between autophagy and disease progression in blood cancer is well exemplified in acute myeloid leukemia (AML) studies. Autophagy deregulation has been described in AML where ATG gene expression is frequently repressed [90,[94][95][96][97]. Autophagy abrogation, by deletion of key ATG genes, leads to leukemia initiation and progression in mouse models [96][97][98][99].…”
Section: Leukemia and Lymphomasmentioning
confidence: 99%
“…Autophagy deregulation has been described in AML where ATG gene expression is frequently repressed [90,[94][95][96][97]. Autophagy abrogation, by deletion of key ATG genes, leads to leukemia initiation and progression in mouse models [96][97][98][99]. Remarkably, some studies showed a high frequency of AML patients, particularly those with complex karyotypes, carrying heterozygous deletions, missense mutations or copy number variations of ATG genes [97,100,101].…”
Section: Leukemia and Lymphomasmentioning
confidence: 99%
“…The PML-RARα phenotype is also characterized by the downregulation of autophagy-related genes (ATGs) (i.e., ULK1, BECN1, ATG14, ATG5, ATG7, ATG3, ATG4B and ATG4C) [29][30][31]. Autophagy or "self-eating" is a highly conserved, closely regulated homeostatic cellular activity that allows for the bulk degradation of long-lived proteins and cytoplasmic organelles [32].…”
Section: Apl Pathophysiologymentioning
confidence: 99%
“…The ubiquitinylation and subcellular localization of PTEN are regulated by a HAUSP-PML network [27], we demonstrated that PML-RARα directly suppresses PTEN expression [28]. The lack of PTEN anticancer control could play a pivotal role in favoring the emergence, survival and proliferation of damaged stem cells, allowing the accumulation of additional genetic events towards leukemogenesis.The PML-RARα phenotype is also characterized by the downregulation of autophagy-related genes (ATGs) (i.e., ULK1, BECN1, ATG14, ATG5, ATG7, ATG3, ATG4B and ATG4C) [29][30][31]. Autophagy or "self-eating" is a highly conserved, closely regulated homeostatic cellular activity that allows for the bulk degradation of long-lived proteins and cytoplasmic organelles [32].…”
mentioning
confidence: 99%